ISO/TR 12300:2016 for clinical cross-terminology mapping: contribution to nursing - Torres, Fernanda Broering Gomes; Gomes, Denilsen Carvalho; Ronnau, Lucas; Moro, Cláudia Maria Cabral; Cubas, Marcia Regina (Revista da Escola de Enfermagem da USP, 2020)
ABSTRACT This theoretical and reflective study aimed to assess the contribution of the ISO/TR 12300:2016 document for the mapping of nursing terminology. The referred document and related articles were used as an empirical framework. The study analyzed the content of the document, highlighting cardinality and equivalence principles. The standard presents conceptual and operational basis for mapping, with cardinality and equivalence as the support for the categorization of cross-terminology mapping in the area of nursing. Cardinality verifies candidate target terms to represent the source term, while the equivalence degree scale checks semantic correspondence. Among the principles included in the ISO/TR 12300:2016, cardinality and equivalence contribute to the accurate representation of the results of the cross-terminology mapping process and its use should decrease inconsistencies.